Prediction effects on internal resonance wave of metallic conductive ink in rotational motion behaviour - Salim, Mohd Azli; Omar, Ghazali; Md. Saad, Adzni; Masripan, Nor Azmmi; Akop, Mohd Zaid; Dai, Feng; Dmitriev, Andrey N.; Naroh, Azmi (Universiti Malaysia Perlis, 2020)
This paper represents the effects on internal resonance wave of metallic conductive ink in rotational motion behaviour. The internal resonance metallic conductive ink model is developed using the wave propagation approach. There are two equations derived from this which are impedance and stiffness. Based on these two equations, the multi-body metallic conductive ink model has been successfully derived in order to observe the behaviour of internal resonance, when force is applied at both ends of the model. The internal resonance wave was predicted, and the results have been recorded, and finally, the location of the internal resonance was identified. The maximum level of frequency recorded was at 10 kHz. It is believed that these results can be used in future analysis of metallic conductive ink in order to evaluate and investigate the range of the conductivity of ink with predictive method.